IMMEDIATE, SIGNIFICANT DECLINE IN CENTRAL AND PERIPHERAL BLOOD PRESSURE WITH CENTRAL ARTERIAL VENOUS ANASTOMOSIS. (June 2018) - Saxena, M.; Sobotka, P.; Balmforth, P.; Mathur, A.; Jain, A.; Rensing, B.; Lobo, M.
Abstract : Objective: Clinical trials have reported the intermediate and long term reductions of blood pressure (BP) following formation of a central iliac arteriovenous anastomosis (cAVA). We present for the first time, the immediate and day one BP changes after the procedure Design and method: This open-label, multicentre, European registry is enrolling patients with a baseline office systolic BP > 140 mmHg, average daytime ambulatory systolic BP > 135 mmHg, and resistant or uncontrolled hypertension due to multidrug intolerances. Subjects underwent arteriovenous (AV) coupler implantation whilst continuing usual medical management. Results: Creation of a cAVA causes immediate, substantial on table reduction of office and ambulatory BP that persists the following day (Table 1). Furthermore, central systolic BP reduced by 23 ± 22 mm Hg (p < 0.0001), central diastolic BP reduced by 13 ± 13 mm Hg (p < 0.0001), and augmentation index (AI) reduced by 39% (p = 0.0006) 1 day after coupler implantation. Figure. No caption available. Conclusions: A significant, instantaneous and day 1 reduction of peripheral and central BP with profound reduction of AI occurs following creation of a cAVA. This magnitude of BP reduction offers the potential to immediately reduce cardiovascular risk associated with hypertension in contrast to alternative therapies for hypertension in which BP reduction takes places over days to weeks.